Empowering Students Through Real Actions and Local Wisdom: Integrating Climate Change Education for Sustainability - Saptono Nugrohadi (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
This article explores the integration of climate change education into chemistry lessons at SMA Negeri 3 Salatiga. The objective is to enhance students' environmental awareness and encourage their active participation in sustainability initiatives. Methods include implementing project-based learning, practical experiments, and collaborative discussions. Results reveal increased student understanding of concepts like the carbon cycle, greenhouse effect, and air pollution through hands-on activities and interdisciplinary approaches. These findings highlight the critical role of chemistry education in fostering environmental responsibility among students.